(untitled) - Salvatore, Dominick (New York, 1992)
The learn-by-doing approach of this powerful study guide helps students master one of the most difficult courses required in most colleges and universities--traditionally one of the most important courses in all economics and business curricula. Every chapter fully illustrates theories, principles or backgrand information and includes multiple-choice review questions with answers.
Keywords: Microeconomics